ASSESSMENT OF DEMOGRAPHIC CAPACITY IN THE CONTEXT OF SPATIAL PLANNING (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The article discusses the issue of demographic capacity assessment in the spatial planning process. Demographic capacity (DC) is the maximum amount of population that can be accommodated in a given area, provided that the daily living requirements of the population are met with local resources, ensuring the ecological balance of the area. The need to calculate the DC stems from the goals and requirements of the proportionately and sustainable development of the area. Due to the complexity of the considered issue, an inventory of the factors determining the DC of the area and justification of their assessment methodology was carried out. DC is a variable quantity that can be changed in the conditions of scientific-technical, socio-economic progress, replenishment of national wealth. In spatial planning, we attach great importance to the integral magnitude of DC assessment. The minimum of the indicators calculated by various factors was accepted as the integrating indicator of the DC. In the article, demographic carrying capacity is calculated according to the following factors: ecological security, territorial opportunities, water resources and recreational resources. As a result of the analysis of private DC, the integrated DC of the studied area is accepted.
Keywords: demographic capacity; population; appropriated zones; permissible load; spatial planning